2021
DOI: 10.3390/ijms22169079
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on the High-Energy Electromagnetic Radiation-Shielding Materials Based on Polymer Nanocomposites

Abstract: This paper revises the use of polymer nanocomposites to attenuate high-energy electromagnetic radiation (HE-EMR), such as gamma radiation. As known, high-energy radiation produces drastic damage not only in facilities or electronic devices but also to life and the environment. Among the different approaches to attenuate the HE-EMR, we consider the use of compounds with a high atomic number (Z), such as lead, but as known, lead is toxic. Therefore, different works have considered low-toxicity post-transitional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 132 publications
(161 reference statements)
1
3
0
Order By: Relevance
“…It should also be noted that when the gamma radiation energy increases, the RPE rates decrease, meaning that these decreases in the RPE rates confirm that all of our results are compatible with the other attenuation parameters (i.e., , , HVL, TVL, MFP) computed and experimentally detected. These conclusions obtained are consistent with the results of the research composites developed for gamma-ray shielding with various nanostructured additives, including polymers [ 11 , 12 , 30 , 31 , 32 , 33 ]. As a result, the current alterations in nanoparticle proportions are quite efficacious for diminishing the influence of gamma radiation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It should also be noted that when the gamma radiation energy increases, the RPE rates decrease, meaning that these decreases in the RPE rates confirm that all of our results are compatible with the other attenuation parameters (i.e., , , HVL, TVL, MFP) computed and experimentally detected. These conclusions obtained are consistent with the results of the research composites developed for gamma-ray shielding with various nanostructured additives, including polymers [ 11 , 12 , 30 , 31 , 32 , 33 ]. As a result, the current alterations in nanoparticle proportions are quite efficacious for diminishing the influence of gamma radiation.…”
Section: Resultssupporting
confidence: 90%
“…Güven’s research focused on radiation-supported production of polymeric nanomaterials, suggesting that these developed materials with high added value will not be limited to existing applications, but will be enriched with different usage properties [ 29 ]. Acevedo-Del-Castillo et al investigated the use of polymer nanocomposites to attenuate the implementation of high-energy irradiation, and found that the increase in the attenuating characteristics of slight, resilient, and well-rounded substances (such as polymeric materials) can be a contribution of upcoming technologies to the acquisition of more influential substances for diminishing the detriment caused to the high-energy electromagnetic radiation (HE-EMR) in several areas where it is found [ 30 ]. Doyan et al worked on the polymeric film materials of polyvinyl alcohol (PVA), trichloroethylene (TCE), and cresol red (CR) dye to expose the gamma beams for eventual implementation in radiation dosimetry; their results indicate that enhancement of the radiation rate altered the hue of the polymeric film, from purple (pH > 8.8) with no radiation (0 kGy) to yellow (nearly pellucid) (2.8 < pH < 7.2) at the uppermost rate (12 kGy); in other words, these results demonstrated a useful dose range of 0–12 kGy for the investigated polymeric film samples [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of rubbers in the production of materials that allow attenuation of this radiation, combined with flexibility properties, can be oriented to versatile applications such as flexible shielding and coating of electronic devices, among others [ 5 ]. As it is well known [ 6 ], lead is the metallic element most often used for radiation attenuation, but this element is toxic both for human health and for the environment. In this context, the bismuth element seems to emerge as a viable alternative to replace lead since it is more environmentally friendly and non-toxic to health [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, electron-irradiation-induced defects have been employed in the engineering of graphene electronic properties [ 17 , 18 , 19 , 20 , 21 ] and, more generally, in sensing applications [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In the case of high-energy electron irradiation, graphene has been mainly employed in composites for radiation shielding applications [ 30 ], therefore structural defects induced by MeV electrons in graphene sheets have been very poorly studied [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%